Thermal Sensation Analysis in the Building of Universitas Ichsan Gorontalo - Siti Khairunnisa Abay; Baharuddin Hamzah; Rosady Mulyadi (Center of Techonolgy (COT), Engineering Faculty, Hasanuddin University, 2022)
Gorontalo City is characterized by a tropical climate, where thermal comfort is a crucial component to achieve, particularly for educational activities aimed at students. The thermal comfort is affected by various factors, namely building design, internal, and external factors. The university building represents a facility where face-to-face learning and teaching activities occur. The purpose of the current study is to analyze the perceived thermal comfort of students during classroom activities with three different air conditioning (AC) settings (16, 22, and 27 oC) in theUniversitas Ichsan Gorontalo campus building. This research employed a quantitative descriptive method, comprising thermal measurements inside the classroom and questionnaire distribution to students to collect thermal sensation data. The research object was conducted in three separate classrooms during the time range of 08.00-15.00 Central Indonesia time. The results revealed that most students felt neutral and comfortable in the three different AC settings inside the classroom. Nevertheless, it should be noted that thermal comfort could be influenced by other factors, such as physical activity and clothing. Consequently, further research could be conducted by taking into consideration these factors and engaging the participation of teachers and staff to acquire a more comprehensive understanding of thermal comfort in the campus building.